PENGARUH KEPUASAN, KOMITMEN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEJABAT PENGADAAN BARANG DAN JASA PROVINSI PAPUA BARAT DAYA - Amir Husin Siregar; Pahmi Pahmi; Mervin Komber; Andi Irwan (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of job satisfaction, organizational commitment, and work environment on the performance of procurement officials in Southwest Papua Province. The research employed a quantitative approach with associative research type. The population consisted of all 53 procurement officials in Southwest Papua Province, and the entire population was sampled using saturated sampling technique. Data were collected using a 4-point Likert scale questionnaire. Data analysis techniques included multiple linear regression, t-test, F-test, and coefficient of determination. The results showed that partially, job satisfaction had a positive and significant effect on performance (coefficient 0.258; sig. 0.044). Organizational commitment had a positive and significant effect with a coefficient of 0.420 (the most dominant; sig. 0.000). Work environment had a positive but non-significant effect (coefficient 0.060; sig. 0.538). Simultaneously, all three variables had a significant effect on performance (F calculated 15.590; sig. 0.000). The R Square value of 0.488 means that the contribution of the three variables to performance is 48.8%, while the remaining 51.2% is influenced by other variables outside the model. In conclusion, organizational commitment is the most dominant factor in improving performance, followed by job satisfaction, while work environment has no significant effect. It is recommended that leadership prioritize strengthening employees' organizational commitment as the main strategy for improving performance, continue to enhance job satisfaction through improving compensation, supervision, and career opportunities, and gradually improve the work environment according to available budget.